Scope of the easements for investment projects: An effective solution to boost mining in Peru? - Pachas Pérez, Diego (2016)
This article analyze the promotion of the Peruvian economy from an Administrative Law perspective. Hereof, it describe the main regulations changes which have generated substantial variations in the process for obtaining several permits, such as environmental management intruments and easement rights, needed for the development of investment projects. In general, those changes are related to the reduction of the terms applicable for its obtainting and the elimination of bureaucracy.In this context, the easement right is one of the most important changes. Hence, its scope, classification, procedure for obtaining and contingencies arise from it are analyzed.Finally, the author proposes an improvent of the legal framework applicable to the easements for the development of mining projects in order to make it a secure way to boost country’s economy.